TERMINOLOGI MANUSIA DAN INSAN KAMIL DALAM PERSPEKTIF AL-QUR’AN DAN IBNU ARABI - Sofyan Rofi; Benny Prasetiya; Bahar Agus Setiawan (Universitas Muhammadiyah Ponorogo, 2020)
Human beings who continue to experience endless debates. Departing from western theory, starting from Aristotle's theory, Louis Pasteur, to Charles Darwin, who tried to rediscover the nature of theÂ origin of life and human life which states that humans actually came from previous lives. Although the theory is often considered rational but in reality, it still raises many questions and doubts regarding the facts of human creation. The purpose of writing is to describe human terminology in Alquran and Ibn Arabi. The expected results are enlightenment about human nature in realizing our human meaning